2011
DOI: 10.1093/mp/ssr046
|View full text |Cite
|
Sign up to set email alerts
|

An Updated GA Signaling ‘Relief of Repression’ Regulatory Model

Abstract: Gibberellic acid (GA) regulates many aspects of plant growth and development. The DELLA proteins act to restrain plant growth, and GA relieves this repression by promoting their degradation via the 26S proteasome pathway. The elucidation of the crystalline structure of the GA soluble receptor GID1 protein represents an important breakthrough for understanding the way in which GA is perceived and how it induces the destabilization of the DELLA proteins. Recent advances have revealed that the DELLA proteins are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 54 publications
1
34
0
1
Order By: Relevance
“…Previous studies have shown that GID1 receptor-mediated GA perception and 26S proteasome-mediated DELLA degradation are necessary for most GA responses (Fu et al, 2002;Ueguchi-Tanaka et al, 2005;de Lucas et al, 2008;Feng et al, 2008;Gao et al, 2011;Sun, 2011). Thus, whether the newly discovered DELLAindependent GA response also relies on GID1-mediated GA reception and 26S proteasome-mediated degradation was tested.…”
Section: Auxin-induced Fruit Elongation Requires Ga Signalingmentioning
confidence: 99%
“…Previous studies have shown that GID1 receptor-mediated GA perception and 26S proteasome-mediated DELLA degradation are necessary for most GA responses (Fu et al, 2002;Ueguchi-Tanaka et al, 2005;de Lucas et al, 2008;Feng et al, 2008;Gao et al, 2011;Sun, 2011). Thus, whether the newly discovered DELLAindependent GA response also relies on GID1-mediated GA reception and 26S proteasome-mediated degradation was tested.…”
Section: Auxin-induced Fruit Elongation Requires Ga Signalingmentioning
confidence: 99%
“…1C; Gao et al, 2011). The effects of GA include promotion of seed germination, stimulation of organ elongation, and induction of flowering.…”
Section: Gamentioning
confidence: 99%
“…GA binding to GID1 results in binding to nucleus-localized growth repressors called DELLA proteins (Ueguchi-Tanaka et al, 2005;Nakajima et al, 2006;Willige et al, 2007). This tripartite GID-GA-DELLA complex is subsequently targeted for ubiquitylation by SCF SLY1/SNZ E3 ligases, resulting in degradation of the DELLAs (Gao et al, 2011). This scenario is reminiscent of UPS action during auxin and JA-Ile signaling, because DELLA proteins bind and repress the activity of transcription factors such as the PHYTOCHROME INTERACTING FACTORs (de Lucas et al, 2008;Feng et al, 2008).…”
Section: Gamentioning
confidence: 99%
“…In this study, we demonstrated that the completely dominant Rht-B1c, an ortholog of Arabidopsis GAI, was caused by a 30-amino acid insertion in the DELLA domain and disrupted the GA-dependent interaction with TaGID1. According to the "relief-of-restraint" model, DELLA proteins restrain plant growth while GA relieves DELLA repression by overcoming DELLA-mediated growth restraint Richards et al, 2001;Silverstone et al, 2001;Harberd, 2003;Jiang and Fu, 2007;Hou et al, 2010;Gao et al, 2011). Binding of bioactive GA to GID1 promotes the interaction of GID1 with the DELLA proteins, the subsequent polyubiquitination of the DELLAs via the E3 ubiquitin-ligase SCF SLY1/GID2 , and the eventual destruction of DELLA proteins in the 26S proteasome (McGinnis et al, 2003;Sasaki et al, 2003;Dill et al, 2004;Fu et al, 2004;Ueguchi-Tanaka et al, 2005;Griffiths et al, 2006;Jiang and Fu, 2007;Murase et al, 2008;Harberd et al, 2009;Hou et al, 2010).…”
Section: Dominance/recessiveness Of Gai Depends On the Level Of Intermentioning
confidence: 99%
“…Binding of bioactive GA to GID1 promotes the interaction of GID1 with the DELLA proteins, the subsequent polyubiquitination of the DELLAs via the E3 ubiquitin-ligase SCF SLY1/GID2 , and the eventual destruction of DELLA proteins in the 26S proteasome (McGinnis et al, 2003;Sasaki et al, 2003;Dill et al, 2004;Fu et al, 2004;Ueguchi-Tanaka et al, 2005;Griffiths et al, 2006;Jiang and Fu, 2007;Murase et al, 2008;Harberd et al, 2009;Hou et al, 2010). Thus, DELLA proteins restrain plant growth while GA promotes growth by targeting the DELLA proteins for degradation (Silverstone et al, 2001;Fu et al, 2002;Gao et al, 2011).…”
Section: Dominance/recessiveness Of Gai Depends On the Level Of Intermentioning
confidence: 99%